Variants and Related Systems - Abe, Jair Minoro [UNESP]; Akama, Seiki; Nakamatsu, Kazumi; Abe, JM; Akama, S; Nakamatsu, K (Springer, 2015)
This chapter reviews some variants of annotated logics and related systems in the literature. Variants include fuzzy annotated logics, possibilistic annotated logics, inductive annotated logics, and structural annotated logics. We also compare annotated logics with related systems such as Labelled Deductive Systems and General Logics. Finally, we review systems of paraconsistent logics.